(untitled) (Research, Society and Development, 2021)
In this research, the potential of sugarcane bagasse as a natural adsorbent of synthetic textile dye was evaluated. In the first stage of the research, the preparation and characterization of the adsorbent was carried out by determining the zero charge point - pHPCZ and Fourier transformation infrared spectroscopy (FTIR), it was found that adsorbent has a pHPCZ equal to 3.37 for dry material at 60 °C. In the second stage of the research, acidic and alkaline activations of adsorbent material were carried out and an experimental planning of the Box-Behnken type 25 for each adsorbent material, having the mass, concentration, pH, rotation and time as independent variables, evaluating adsorbed quantity responses (qt) and reduction in dye concentration (%red). The kinetic tests were performed at pH 3.0 and concentration of 150 mg.L-1, with samples collected every five minutes for up to 60 minutes, for fresh, acid and alkaline adsorbents. The kinetic data were adjusted to models of pseudo-first order, pseudo-second order and Elovich equation, with Elovich model being best adjusted to the tests. The isotherms were constructed varying concentration from 25 to 200 mg. L-1, with pH 3.0 and the Sips isotherm obtained a higher value of R2 and Test F. The sugarcane bagasse was attractive in the removal of the direct dye Tupy® burgundy 16, especially when the adsorbent treatment with HCl is carried out.